Memahami Pribumisasi Islam Melalui Kitab Seribu Masalah - Oman Fathurahman (Studia Islamika, 2012)
Book Review: Ronit Ricci, Islam Translated: Literature, Conversion, and the Arabic Cosmopolis of South and Southeast Asia, Chicago and London: The University of Chicago Press, xxii + 316 halaman, 2011.For the time when Islam spread, was adopted and also translated into a variety of traditions and cultures, a comparative studies model such as the one done by Ronit Ricci in Islam Translated has became a very important contribution. The long history of Islamization and conversion has given birth to many Islamic civilizations, including in Southeast Asia. A monolithic view or endless debate related to the origin of sources for the coming of Islam to this region, or the central–periphery perspective that dichotomizes Islam at Mecca and Medina as the ‘original’ and Islam in other places as ‘not pure’, has become not relevant anymore. For understanding the phenomena of Islam in Southeast Asia, the author of this book provides discourse on the processes of communication, contacts, networks, diasporas, interaction and transmission that happened in Muslim circles through a variety of different texts in Kitab Seribu Masalah.DOI: 10.15408/sdi.v19i3.359